Historical performance and future climate projections from CMIP6 models in central-eastern Argentina - Muller, Gabriela Viviana (2025)
This paper analyses historical climate conditions and future climate projections in central-easternArgentina, focusing on temperature and precipitation patterns. The study assesses the ability ofCoupled Model Intercomparison Project Phase 6 (CMIP6) global climate models to representhistorical climate variability and generates projections of precipitation and temperature underthree combined socioeconomic and greenhouse gas emissions scenarios for the 21st Century.Historical analysis for the 1901–2014 period reveals high correlations between model-simulatedand observed temperature. Precipitation simulations are less accurate; however, bias correctionintroduces notable improvements. Although the models properly recognise mean annual temperature and precipitation cycles, biases appear in the reproduction of the spatial patterns ofthese variables. Future projections indicate a significant increase in mean annual temperatureacross all scenarios, with the highest temperature rise in a fossil-fuel-intensive scenario, highlighting the importance of emissions mitigation. Precipitation is projected to increase in allscenarios, particularly in the western part of the study region, with potential implications forhydrology and agriculture. This study emphasises the need for ongoing research and monitoringto enhance our understanding of regional climate vulnerability and to inform local adaptationstrategies in the face of a changing climate.